Retrieval shifts in spatial skill acquisition are collective rather than item-specific. - Frank, David J.; Macnamara, Brooke N. (Memory & Cognition, 2019)
How do people improve their ability to intercept moving targets? Prior research and theories of skill acquisition suggest that individuals engage in item-specific retrieval shifts (Anglim & Wynton, 2015; Logan, 1988; Palmeri, 1997; Rickard, 1997, 2004; Touron, 2006; Wilkins & Rawson, 2010). However, this prior research examined performance on nonspatial, nondynamic tasks. In three experiments, we pitted four hypotheses against each other, to test skill acquisition for intercepting repeated trajectories in a spatial and dynamic task: the item-specific algorithmic speedup hypothesis, the item-specific retrieval shift hypothesis, the collective retrieval shift hypothesis, and the combined hypothesis (item-specific algorithmic speedup followed by a collective retrieval shift). We found evidence for the combined hypothesis. Specifically, under easy conditions, we found small improvements on repeated trajectories that were attributable to item-specific algorithmic speedup. By contrast, under difficult conditions, we found strong evidence that the performance benefits for repeated trajectories were driven primarily by a collective shift from algorithmic to direct-retrieval strategies. This evidence for collective retrieval shift is in direct contrast to theories suggesting item-specific retrieval shifts. Theoretical and practical implications are discussed.